1995
DOI: 10.1139/b95-178
|View full text |Cite
|
Sign up to set email alerts
|

Native prairie grasses and microbial community responses to reclamation of taconite iron ore tailing

Abstract: The effect of reclamation treatments on seeded native grass cover and species composition, soil microbial biomass carbon, and populations of actinomycetes, fungi, free-living N2-fixing bacteria, and aerobic heterotrophic bacteria was compared in field plots in coarse taconite tailing. Reclamation treatments consisted of all possible combinations of three rates of composed yard waste, three rates of fertilizer, and inoculation with arbuscular mycorrhizal fungi. Composted yard waste increased plant cover, soil m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…Microbial and fungal activity is important for restoration of mine tailings, establishment of plants and biogeochemical cycling (Noyd et al, 1995), particularly in acid mine drainage (Mills, 1985). Microorganisms change the bioavailability of heavy metals, solubilization of minerals in mine tailings, release nutrients, supply them to the plants, and enhance plant growth (Moynahan et al, 2002;Wu et al, 2006).…”
Section: Phytoremediation Of Mine Waste Depositsmentioning
confidence: 99%
“…Microbial and fungal activity is important for restoration of mine tailings, establishment of plants and biogeochemical cycling (Noyd et al, 1995), particularly in acid mine drainage (Mills, 1985). Microorganisms change the bioavailability of heavy metals, solubilization of minerals in mine tailings, release nutrients, supply them to the plants, and enhance plant growth (Moynahan et al, 2002;Wu et al, 2006).…”
Section: Phytoremediation Of Mine Waste Depositsmentioning
confidence: 99%
“…The establishment of vegetation on contaminated soils could be difficult due to metal toxicity, low nutrient content, degraded microbial communities and poor physical structure of the substrate (Noyd et al, 1995;Ussiri and Lal, 2009). Despite the high tolerance observed in Miscanthus, several studies have shown that TEs induce a reduction of its aerial biomass (Ezaki et al, 2008;Sharmin et al, 2012;Wanat et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Because weedy plants usually respond better to fertilization than warm-season prairie grasses, this result may be due to increased mycorrhizal infectivity as weedy grasses did not diminish with increasing application rate but prairie grasses increased. A study conducted on iron mine tailings in Minnesota found that composted yard waste significantly increased vesicular-arbuscular mycorrhizal infectivity compared to inoculation using some of the same species planted in this study and that available P increased more in the plots amended with the compost than with fertilizers (Noyd et al 1995;Noyd, Pfleger, and Norland 1996). However, given that soil P levels only increased in the depths where pulp was incorporated, decomposition of the Fluff and subsequent mineralization of P was most likely responsible, regardless of the effect of pulp on mycorrhizal infection.…”
Section: Soil Analysismentioning
confidence: 48%